A 13,100-year record of net primary productivity from subtropical China reveals shifting climatic and anthropogenic controls - Lin Zhao; Shanshan Meng; Zijian Liu; Tengwen Long; Zhiguo Rao; Haibin Wu (Anthropocene, 2026)

A quasi-zero stiffness locally resonant metamaterial with tunable low-frequency and wide bandgap - Haibin Ding; Chenghui Lin; Changjie Xu; C.W. Lim; Zhiyun Liu; Yitian Yu; Lihong Tong (Engineering Structures, 2026)

Continuous Planting Reshapes Root Endophytic Microbes and Drives Growth Decline in Casuarina equisetifolia - Lei Hong; Yuhua Wang; Mingzhe Li; Jianjuan Li; Qingxu Zhang; Miaoen Qiu; Xiaoli Jia; Qingui Su; Wenxiong Lin; Haibin Wang; Zeyan Wu (Indian Journal of Microbiology, 2026)

Reliability Enhancement of Underwater Acoustic Communication in Dynamic Underwater Channels via Unequal-Rate Frequency–Phase Signaling - Yining Lin; Yupeng Tai; Chenghao Hu; Yonglin Zhang; Jun Wang; Haibin Wang (Journal of Marine Science and Engineering, 2026)
Underwater acoustic (UWA) channels are inherently complex, with pronounced variability arising from multipath propagation, time variability, Doppler effects, and nonstationary ocean conditions. Such variability often leads to unstable communication reliability when conventional single-carrier signaling and fixed reception strategies are employed. In practical UWA environments, performance degradation may occur when channel characteristics deviate from the assumed regime, thereby limiting system robustness. To address this reliability challenge, this study develops an unequal-rate frequency–phase keying (URFPK) signaling strategy that combines a low-rate frequency component with a high-rate phase component. A corresponding receiver structure is designed, employing parallel coherent and noncoherent processing to enhance robustness under dynamic channel conditions. In addition, a reduced-complexity noncoherent procedure is introduced to improve computational efficiency. Simulation results demonstrate substantially improved robustness under severe UWA distortions. Full-scale sea trials further validate the engineering effectiveness of the proposed approach, achieving communication success rate improvements of 18.62% and 9.39% over baseline schemes within short intervals and maintaining an overall success rate exceeding 91% over extended transmissions. These results indicate that the URFPK signaling strategy provides a practical and robust mechanism for improving UWA link reliability in dynamic UWA channels.

Why does tropical cyclone Emeraude move along a small annular track? - Yaoyao Zhou; Lixiang Shen; Ziqiong Cheng; Lin Peng; Rufa’i Isyaku; Haibin Lü (Journal of Earth System Science, 2026)

Real-world VOCs from ethanol gasoline vehicles: Speciation, ozone formation potential, and inter-city differences - Ziyang Zhang; Jing Li; Jun Li; Hairong Cheng; Haibin Huang; Jianchu Ma; Boji Lin; Gan Zhang (Journal of Hazardous Materials, 2026)

Deep learning-based species identification of gymnosperm xylem: The practice in digital forestry - Chang Zheng; Tuo He; Lichao Jiao; Yang Lu; Shoujia Liu; Tianxiao Li; Yuanyuan Miao; Dejun Feng; Jian Lin; Xian Feng; Zhonghua Huang; Min Yu; et al. (Computers and Electronics in Agriculture, 2025)

Ultra-stretchable, tough, transparent dermis matrix gel sensors integrated with GCQDs and WO3NPs for visual UVI detection and real-time human motion/temperature sensing - Jialu Shen; Pengtao Zu; Jinwei Zhang; Wei Lin; Haibin Gu (Chemical Engineering Journal, 2025)

Dual-mode demodulation method for robust underwater acoustic communication - Yining Lin; Yupeng Tai; Chenghao Hu; Yonglin Zhang; Jun Wang; Longxu Wang; Haibin Wang (Ocean Engineering, 2025)

Effect of intercropping with forage soybean on the rhizosphere soil nutrients of tea plants - Yuhang Jiang; Xiaoqin Lin; Haibin Wang; Yina Xu; Wenxiong Lin (CATENA, 2025)

The AHL-driven cascade of rhizosphere microbes, enzymes, and nutrients contributes to the growth decline of Casuarina equisetifolia in continuous planting systems - Qingxu Zhang; Yi Lin; Lei Hong; Yuhua Wang; Miaoen Qiu; Jianjuan Li; Tingting Wang; Zongnan Wu; Mingmei Wu; Wenxiong Lin; Haibin Wang; Zeyan Wu (Rhizosphere, 2025)

HDAC9 Deficiency Upregulates cGMP-dependent Kinase II to Mitigate Neuronal Apoptosis in Ischemic Stroke - Haoran Lin; Yun Bei; Zexu Shen; Taofeng Wei; Yuyang Ge; Lingyan Yu; Huimin Xu; Wei He; Yunjian Dai; Difei Yao; Haibin Dai (Translational Stroke Research, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Dabrafenib upregulates hypoglycosylated MUC1 and improves the therapeutic efficacy of Tn-MUC1 CAR-T cells - Ziwei Zhou; Yinghua Zhu; Jianli Zhao; Yiming Zhao; Wenkui Fu; Chao Zhou; Jinfang Hu; Yewen Zeng; Yiguang Lin; Hong An; Haibin Yin; Herui Yao; et al. (Science Bulletin, 2025)

Using DNA metabarcoding to assess insect diversity in grasslands - Changjin Lin; Haibin Han; Kejian Lin; Hongmei Cheng; Luyao Fu; Muhammad Ashfaq; Paul D. N. Hebert; Chenxi Liu (Applied Entomology and Zoology, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Chronic exposure to liquid crystal monomer EBCN at environmentally relevant concentrations induces testicular dysfunction via the gut-testis axis - Jun Wu; Daojun Lv; Wanmei Lin; Yiyou Mao; Yanqing Xia; Leilei Feng; Tianxin Zhao; Xiangming Mao; Fangpeng Shu; Haibin Guo (Journal of Hazardous Materials, 2025)

Enzymatic degradation of polybutylene succinate by recombinant cutinase cloned from Paraphoma chrysanthemicola - Jingwei Lin; Kexin Sun; Li Ma; Chunwang Li; Haibin Tong; Zhanyong Wang (Journal of Environmental Management, 2025)

Contrasting orbital rhythms preserved in loess grain-size records across the Chinese Loess Plateau - Deai Zhao; Guoqiao Xiao; Chunju Huang; Haibin Wu; Qingzhen Hao; David B. Kemp; Shaohua Tian; Zhipeng Wu; Hao Lu; Gaowen Dai; Shuzhen Peng; Changyan Tang; et al. (Global and Planetary Change, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Shifting ceria’s function from inhibitor to promotor by oxygen vacancies - Hongfei Lin; Haibin Yin; Bo Wu; Hongliang Li; Jie Zeng (Science Bulletin, 2024)

Uncovering and preventing polytellurides dissolution enables stable sodium-ion storage: A case study of SnTe - Zhixin Liang; Jianlian Huang; Wei Zhang; Heying Chu; Qinghua Li; Haibin Lu; Zeyu Lin; Junling Wang; Haiping Lin; Yuyang Chen; Shiyun Xiong; Shaoming Huang (Chemical Engineering Journal, 2024)

Ozone sensitivity regimes vary at different heights in the planetary boundary layer - Xin Li; Wenjie Wang; Suding Yang; Yafang Cheng; Limin Zeng; Xuena Yu; Sihua Lu; Ying Liu; Min Hu; Shaodong Xie; Xiaofeng Huang; Jun Zhou; et al. (Science of The Total Environment, 2024)

AlphaFold-guided redesign of a plant pectin methylesterase inhibitor for broad-spectrum disease resistance - Yeqiang Xia; Guangzheng Sun; Junhua Xiao; Xinyi He; Haibin Jiang; Zhichao Zhang; Qi Zhang; Kainan Li; Sicong Zhang; Xuechao Shi; Zhaoyun Wang; Lin Liu; et al. (Molecular Plant, 2024)

Perovskite intermediate phase FAPbBr3·DMSO assisted in-situ growth of FAPbBr3 polycrystalline wafer for X-ray detection and imaging - Dan Liu; Wei Jiang; Siyin Dong; Haipeng Di; Haibin Li; Zhenning Xing; Hongbing Wang; Jiwei Ren; Xiaojia Zheng; Lin Lei; Yiying Zhao (Chemical Engineering Journal, 2024)

Ratiometric fluorescence sensor based on deep learning for rapid and user-friendly detection of tetracycline antibiotics - Zhengjie Chen; Zhi Li; Haibin He; Juhua Liu; Junjie Deng; Lin Jiang; Xinghai Liu (Food Chemistry, 2024)

Modeling the mid-piacenzian warm climate using the water isotope-enabled Community Earth System Model (iCESM1.2-ITPCAS) - Yong Sun; Lin Ding; Baohuang Su; Harry Dowsett; Haibin Wu; Jun Hu; Christian Stepanek; Zhongyu Xiong; Xiayu Yuan; Gilles Ramstein (Climate Dynamics, 2024)
The mid-Piacenzian Warm Period (MPWP, ~ 3.264–3.025 Ma) is the most recent example of a persistently warmer climate in equilibrium with atmospheric CO 2 concentrations similar to today. Towards studying patterns and dynamics of a warming climate the MPWP is often compared to today. Following the Pliocene Model Intercomparison Project, Phase 2 (PlioMIP2) protocol we prepare a water isotope-enabled Community Earth System Model (iCESM1.2) simulation that is warmer and wetter than the PlioMIP2 multi-model ensemble (MME). While our simulation resembles PlioMIP2 MME in many aspects we find added insights. (1) Considerable warmth at high latitudes exceeds previous simulations. Polar amplification (PA) is comparable to proxies, enabled by iCESM1.2’s high climate sensitivity and a distinct method of ocean initialization. (2) Major driver of warmth is the downward component of clear-sky surface long-wave radiation ( $$\varDelta T_{\text{rlds}_\text{clearsky}}$$ Δ T rlds _ clearsky ). (3) In iCESM1.2 modulated dominance of dynamic (δDY) processes causes different low-latitude (~ 30 S°–10°N) precipitation response than the PlioMIP2 MME, where thermodynamic processes (δTH) dominate. (4) Modulated local condensation leads to lower δ18O p across tropical Indian Ocean and surrounding Asian-African-Australian monsoon regions. (5) We find contrasting changes in tropical atmospheric circulations (Hadley and Walker cells). Anomalous regional meridional (zonal) circulation, forced by changes in tropical-subtropical (tropical) diabatic processes, presents a more comprehensive perspective than explaining weakened and expanded Hadley circulation (strengthened and westward-shifted Walker circulation) via static stability. (6) Enhanced Atlantic meridional overturning circulation owes to a closed Bering Strait.

PLD2 deletion ameliorates sepsis-induced cardiomyopathy by suppressing cardiomyocyte pyroptosis via the NLRP3/caspase 1/GSDMD pathway - Jun Li; Da Teng; Wenjuan Jia; Lei Gong; Haibin Dong; Chunxiao Wang; Lihui Zhang; Bowen Xu; Wenlong Wang; Lin Zhong; Jianxun Wang; Jun Yang (Inflammation Research, 2024)
Objective Sepsis-induced cardiomyopathy (SICM) is a life-threatening complication. Phospholipase D2 (PLD2) is crucial in mediating inflammatory reactions and is associated with the prognosis of patients with sepsis. Whether PLD2 is involved in the pathophysiology of SICM remains unknown. This study aimed to investigate the effect of PLD2 knockout on SICM and to explore potential mechanisms. Methods The SICM model was established using cecal ligation and puncture in wild-type and PLD2-knockout mice and lipopolysaccharide (LPS)-induced H9C2 cardiomyocytes. Transfection with PLD2-shRNA lentivirus and a PLD2 overexpression plasmid were used to interfere with PLD2 expression in H9C2 cells. Cardiac pathological alterations, cardiac function, markers of myocardial injury, and inflammatory factors were used to evaluate the SICM model. The expression of pyroptosis-related proteins (NLRP3, cleaved caspase 1, and GSDMD-N) was assessed using western blotting, immunofluorescence, and immunohistochemistry. Results SICM mice had myocardial tissue damage, increased inflammatory response, and impaired heart function, accompanied by elevated PLD2 expression. PLD2 deletion improved cardiac histological changes, mitigated cTNI production, and enhanced the survival of the SICM mice. Compared with controls, PLD2-knockdown H9C2 exhibits a decrease in inflammatory markers and lactate dehydrogenase production, and scanning electron microscopy results suggest that pyroptosis may be involved. The overexpression of PLD2 increased the expression of NLRP3 in cardiomyocytes. In addition, PLD2 deletion decreased the expression of pyroptosis-related proteins in SICM mice and LPS-induced H9C2 cells. Conclusion PLD2 deletion is involved in SICM pathogenesis and is associated with the inhibition of the myocardial inflammatory response and pyroptosis through the NLRP3/caspase 1/GSDMD pathway.

Microcystin-RR promote lipid accumulation through CD36 mediated signal pathway and fatty acid uptake in HepG2 cells - Wenjuan Jia; Lin Zhong; Qingmiao Ren; Da Teng; Lei Gong; Haibin Dong; Jun Li; Chunxiao Wang; Yong-Xing He; Jun Yang (Environmental Research, 2024)

Analysis of environmental selection pressure of superoxide dismutase in deep-sea sea cucumber - Yanan Li; Zongfu Chen; Haibin Zhang; Ruoyu Liu; Shuichun Chen; Li Lin (Journal of Oceanology and Limnology, 2024)

Development and application of electrospun fiber-based multifunctional sensors - Xing Chen; Junhao Wang; Jiangtao Zhang; Haibin Lin; Meng Tian; Mengchao Li; Ye Tian (Chemical Engineering Journal, 2024)

Genome-wide identification and functional analysis of the cellulose synthase-like gene superfamily in common oat (Avena sativa L.) - Shanshan Zhang; Haibin Hu; Shumin Cui; Lin Yan; Bing Wu; Shanjun Wei (Phytochemistry, 2024)

Mechanisms underlying palmitic acid-induced disruption of locomotor activity and sleep behavior in Drosophila - Yumei Huang; Jiaqi Zhang; Dongdong You; Shangqin Chen; Zhongdong Lin; Boyang Li; Menglai Ling; Haibin Tong; Feng Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Quaternary evolution of the Dunhuang paleolake and its controlling factors in the northeastern Tibetan Plateau - Jianlei Zheng; Jinjiang Zhang; Bo Zhang; Yang Wang; Daxiang Gu; Lin Feng; Haibin Wang (Geomorphology, 2023)

Identification of a soil water flow equation using a two-step data-driven method - Yakun Wang; Qiuru Zhang; Liangsheng Shi; Haibin Chang; Wenxiang Song; Lin Lin; Xiaolong Hu; Xiaotao Hu (Journal of Hydrology, 2023)

Phod-harboring bacterial communities mediated slow and fast phosphorus transformation in alkaline soil of a Robinia pseudoacacia afforestation chronosequence - Ying Wang; Lin Yang; Jiawen Zhang; Yan Li; Haibin Kang; Xiaoxiong Bai; Yongxing Cui; Min Zhang; Liguo Dong; Xuan Yu (Plant and Soil, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Biodegradation of polylactic acid by a mesophilic bacteria Bacillus safensis - Yujun Wang; Ting Hu; Wanting Zhang; Jinwei Lin; Zhanyong Wang; Shuxia Lyu; Haibin Tong (Chemosphere, 2023)

Desulfurization performance of chemical looping conversion using red mud as an oxygen carrier - Hongming Jiang; Shuchang Yan; Jingzhi Yan; Chengyang Li; Yan Lin; Zengli Zhao; Zhen Huang; Hongyu Huang; Haibin Li (Chemical Engineering Journal, 2023)

Research on Intelligent Trajectory Control Method of Water Quality Testing Unmanned Surface Vessel - Yong Xiong; Haibin Zhu; Lin Pan; Jiying Wang (Journal of Marine Science and Engineering, 2022)
In this paper, we take a water quality testing Unmanned Surface Vessel (USV) as the research object. We propose a heading keeping strategy based on Human Simulated Intelligent Control (HSIC) algorithm and a trajectory tracking strategy under line-of-sight (LOS) algorithm. The practicality of the proposed control strategies was verified by combining simulations and experiments. The main contents were constructed with three parts: Firstly, we designed a complete control system of a water quality inspection unmanned boat with Arduino microcontroller as the core processor. Secondly, we derived the mathematical model of motion after reasonable simplification. Combined with the cycle experiment, the mapping relation between virtual rudder angle and motor speed was established. Then, the USV heading direction control strategy of HSIC was presented and the reliability of the proposed strategy was verified by the course control experiment of USV. Finally, aiming at the defects and shortcomings of the upper-level trajectory tracking LOS algorithm in practical application, we propose the trajectory correction and precise steering control strategies, and the practicality of the improved algorithm was verified by multi-point trajectory tracking experiments. The autonomous fixed-point water quality testing experiment was designed and verified the effectiveness of the proposed strategies.

Serum Neurofilament Light: a Potential Diagnostic and Prognostic Biomarker in Obstetric Posterior Reversible Encephalopathy Syndrome - Xiaobo Fang; Yanling Liang; Weixi Zhang; Qiong Wang; Jingsi Chen; Jia Chen; Yongqiang Lin; Yanli Chen; Li Yu; Haibin Wang; Dunjin Chen (Molecular Neurobiology, 2021)

In silico design of antimicrobial oligopeptides based on 3D-QSAR modeling and bioassay evaluation - Guangping Li; Yuxuan Wang; Yan Shen; Haiqiong Guo; Qingxiu He; Yong Hu; Haibin Liu; Zhihua Lin; Yuanqiang Wang (Medicinal Chemistry Research, 2021)

The contrasting effects of thermodynamic and dynamic processes on East Asian summer monsoon precipitation during the Last Glacial Maximum: a data-model comparison - Yong Sun; Haibin Wu; Masa Kageyama; Gilles Ramstein; Laurent Z. X. Li; Ning Tan; Yating Lin; Bo Liu; Weipeng Zheng; Wenchao Zhang; Liwei Zou; Tianjun Zhou (Climate Dynamics, 2021)
The Last Glacial Maximum (LGM; 21 ka BP) was the most recent glacial period when the global ice sheet volume was at a maximum. Therefore, the LGM can be used to investigate atmospheric dynamics under a climate that differed significantly from the present. This study quantitatively compares pollen records of boreal summer (June–July–August) precipitation with the PMIP3 LGM simulations. The data-model comparison shows an overall agreement on a drier than pre-industrial East Asian summer monsoon (EASM) climate. Nevertheless, 17 out of 55 records show a regional precipitation increase that is also simulated over the additional land mass area due to sea level drop. The thermodynamic and dynamic responses are analyzed to explain a drier LGM EASM as a combination of these two antagonistic mechanisms. Relatively low atmospheric moisture content was the main thermodynamic control on the lower LGM (relative to pre-industrial levels) EASM precipitation amounts in both the reconstructions and the models. In contrast, two dynamic processes in relation to stationary eddy activity act to increase EASM precipitation regionally in records and simulations, respectively. Precipitation increase in records is explained by dynamic enhancement of the horizontal moisture transport, while dynamic enhancement of the vertical moisture transport leads to simulated precipitation increase over the specific region where landmass was exposed during LGM along continental coastlines of China due to significant drop in sea level (relative to pre-industrial levels). Overall, the opposing effects of thermodynamic and dynamic processes on precipitation during the LGM provide a means to reconcile the spatial heterogeneity of recorded precipitation changes in sign, although data-model comparison suggests that the simulated dynamic wetting mechanism is too weak relative to the thermodynamic drying mechanism over data-model disagreement regions.

Identification of 5S and 45S rDNA sites in Chrysanthemum species by using oligonucleotide fluorescence in situ hybridization (Oligo-FISH) - Jun He; Sisi Lin; Zhongyu Yu; Aiping Song; Zhiyong Guan; Weimin Fang; Sumei Chen; Fei Zhang; Jiafu Jiang; Fadi Chen; Haibin Wang (Molecular Biology Reports, 2021)

Rediscovery of the abyssal species Peniagone leander Pawson and Foell, 1986 (Holothuroidea: Elasipodida: Elpidiidae): the first record from the Mariana Trench area - Lin Gong; Xinzheng Li; Ning Xiao; Lisheng He; Haibin Zhang; Yong Wang (Journal of Oceanology and Limnology, 2020)

Anatomical reduction and precise internal fixation of intra-articular fractures of the distal radius with virtual X-ray and 3D printing - Jing Xu; Guodong Zhang; Zaopeng He; Shizhen Zhong; Yongshao Chen; Chunrong Wei; Yudong Zheng; Haibin Lin; Wei Li; Wenhua Huang (Physical and Engineering Sciences in Medicine, 2020)
To evaluate and precisely internal fix intra-articular distal radial fracture (IDRF) using the virtual X-ray and three-dimensional (3D) printing technologies. Twenty-one patients with IDRF were recruited, and the data from digital design group (DDG) and real surgery group (RSG) were collected and analyzed. In DDG, the data from thin-slice computed tomography scan, virtual X-ray measurement parameters, including volar tilt, palmar tilt, radius length (D1), ulnar variation (D2), locking plate position parameter (D3) and distance between key nail and joint surface (D4) were collected. The bone was virtually fixed with the locking plate, and the final model of radius with the screw was obtained by 3D printing. In RSG, the locking plate was precisely pre-bended and used in surgery. During the surgery, the key K-wire was accurately placed and the locking plate was adjusted with the aid of the U-shaped navigation arm. The C-arm was used to observe the positions of key K-wires and the locking plate, and the same above-mentioned parameters were measured intra- and post-operatively. The data from RSG and DDG were compared statistically by t test. This approach proved to be successful in all 21 patients, and none of the screws pierced through the wrist joint surface. All the measured parameters, including the volar tilt, palmar tilt, D1–4, in RSG were not significantly different from preoperative DDG data. Virtual X-ray measurement of anatomical reduction parameters and 3D printing can help the anatomical reduction and precise internal fixation by providing quantitative references, preoperatively, intraoperatively and postoperatively.

Quantitative climatic reconstruction of the Last Glacial Maximum in China - Haibin Wu; Qin Li; Yanyan Yu; Aizhi Sun; Yating Lin; Wenqi Jiang; Yunli Luo (Science China Earth Sciences, 2019)

Sox11-modified mesenchymal stem cells accelerate cartilage defect repair in SD rats - Liangliang Xu; E Shunmei; Sien Lin; Yonghui Hou; Weiping Lin; Wei He; Haibin Wang; Gang Li (Cell and Tissue Research, 2019)

Evolution of the relative abundance of C 4 plants on the Chinese Loess Plateau since the Last Glacial Maximum and its implications - Wenqi Jiang; Jianyu Wu; Haibin Wu; Qin Li; Yating Lin; Yanyan Yu (Journal of Quaternary Science, 2019)
Understanding the distribution of C 3 and C 4 plants and its forcing mechanisms since the Last Glacial Maximum (LGM) is important for anticipating their possible response to future climate change. The spatiotemporal pattern of C 4 plant abundance on the Chinese Loess Plateau (CLP) is complex and the dominant causal factors are contentious. Here, we use δ 13 C records of organic matter in paleosols from the CLP to reconstruct changes in the representation of C 4 plants since the LGM. The results indicate that the relative abundance of C 4 plants increased after the LGM, reaching a maximum during 10–6 ka bp, and then decreased. Spatially, the representation of C 4 plants was characterized by increasing values from north‐west to south‐east. In addition, the smallest spatial difference (∼10%) in the representation of C 4 plants between the north‐west and south‐east parts of the CLP was during the LGM, and the largest difference (∼30%) was during the early Holocene. We combined our findings with output from the BIOME4 model to study the sensitivity of C 4 plants to changes in climate and atmospheric CO 2 concentration. The results suggest that increasing temperature was the dominant factor driving C 4 plant expansion on the CLP since the LGM.

Antiplatelet Strategies and Outcomes in Patients with Noncardioembolic Ischemic Stroke from a Real-World Study with a Five-Year Follow-Up - Huimin Xu; Yanting Ping; Haoran Lin; Ping He; Wenlu Li; Haibin Dai (Translational Stroke Research, 2017)

Physiological characteristics and metabolomics of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene under high temperature stress - Xueli Qi; Weigang Xu; Jianzhou Zhang; Rui Guo; Mingzhong Zhao; Lin Hu; Huiwei Wang; Haibin Dong; Yan Li (Protoplasma, 2017)

Detection of Urine C2C and Trace Element Level in Patients with Knee Osteoarthritis - Gang He; Xuanhuang Chen; Guodong Zhang; Haibin Lin; Rongyi Li; Xianwei Wu (Cell Biochemistry and Biophysics, 2014)

Short-Term Effect of Unilateral Pedicle Screw Fixed Intervertebral Fusion in Treatment of Degenerative Disc Disease Via MAST QUADRANT Minimally Invasive System - Xuanhuang Chen; Changfu Wu; Haibin Lin; Guodong Zhang; Rongyi Li (Cell Biochemistry and Biophysics, 2014)

Precise mapping Fhb5, a major QTL conditioning resistance to Fusarium infection in bread wheat (Triticum aestivum L.) - Shulin Xue; Feng Xu; Mingzhi Tang; Yan Zhou; Guoqiang Li; Xia An; Feng Lin; Haibin Xu; Haiyan Jia; Lixia Zhang; Zhongxin Kong; Zhengqiang Ma (Theoretical and Applied Genetics, 2011)

Fine mapping Fhb4, a major QTL conditioning resistance to Fusarium infection in bread wheat (Triticum aestivum L.) - Shulin Xue; Guoqiang Li; Haiyan Jia; Feng Xu; Feng Lin; Mingzhi Tang; Yao Wang; Xia An; Haibin Xu; Lixia Zhang; Zhongxin Kong; Zhengqiang Ma (Theoretical and Applied Genetics, 2010)

A high-density intervarietal map of the wheat genome enriched with markers derived from expressed sequence tags - Shulin Xue; Zhengzhi Zhang; Feng Lin; Zhongxin Kong; Yong Cao; Chunjun Li; Hongying Yi; Mingfeng Mei; Huilan Zhu; Jizhong Wu; Haibin Xu; Dongmei Zhao; et al. (Theoretical and Applied Genetics, 2008)